2016
DOI: 10.2197/ipsjjip.24.237
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Physical Characteristics with Body-worn Accelerometers Based on Activity Similarities

Abstract: This paper describes our experimental investigation of the end user physical characteristics (e.g., gender, height, weight, dominant hand, and skill at sport) that can be successfully estimated solely from sensor data obtained during daily activities (e.g., walking and dish washing) from body-worn accelerometers. For this purpose we use the huge quantities of data that we have collected, which include 14,880 labeled activities obtained from 61 subjects. Our proposed method tries to estimate various kinds of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In fact, recordings from a single inertial sensor can be employed to deduce the gender, age and height of a user 13 . In this respect, Masuda and Maekawa have also shown that user characteristics (gender, height, weight, dominant hand) can be estimated with machine learning strategies uniquely from basic activities such as washing dishes or walking 14 .…”
Section: Related Workmentioning
confidence: 99%
“…In fact, recordings from a single inertial sensor can be employed to deduce the gender, age and height of a user 13 . In this respect, Masuda and Maekawa have also shown that user characteristics (gender, height, weight, dominant hand) can be estimated with machine learning strategies uniquely from basic activities such as washing dishes or walking 14 .…”
Section: Related Workmentioning
confidence: 99%
“…Algorithmic inferences on audio data can reveal a wide range of potentially private information, such as one's height and weight [17], emotional state [18], [19], and health conditions [19]. Motion sensor data collected by inertial measurement units can also reveal information about an individual's physical characteristics, such as height and weight [20], level of activity [21], and changes in behavioral patterns [22]. These data may be protected with PETs developed for other types of devices and that use transformations of the data [23].…”
mentioning
confidence: 99%